A Tool for Supplementing Mapping Efforts in the Developing World (Journal of Science and Technology, 2016)
The progress in the total map coverage of the land masses of most developing nations is too slow and insufficient in respect of the exploitation of their natural resources. The image map which evolved some few years back from satellite has become a useful alternative cartographic product capable of depicting land use and land cover conditions within a short period of time and at a lower cost compared to classical line maps. The cost associated with image mapping is reasonably affordable, however, the problem of resolution and contrast often affects interpretation of planimetric details. The means of production also can easily be supported by an existing mapping system in a developing world.